Death Anxiety and Impact on Quality of Life in Hemodialysis Patients with Chronic Kidney Disease - Oktavia, Windiyana Putri; Nugroho, Setyo Adi; Munir, Zainal (Jurnal Keperawatan Profesional, 2025)
Chronic Kidney Disease (CKD) is one of the chronic diseases whose prevalence continues to increase globally. CKD patients undergoing hemodialysis therapy not only experience physical burdens but also psychological stress, including anxiety about death (death anxiety), which can impact their quality of life. This study aims to determine the relationship between the level of death anxiety and the quality of life of CKD patients undergoing hemodialysis therapy. This study uses a descriptive correlational quantitative approach and total sampling technique. There were 108 respondents who met the inclusion criteria at Dr. Mohammad Saleh Regional General Hospital in Probolinggo City. The research instruments used were the Death Anxiety Questionnaire and WHOQOL-BREF. The results showed that most patients had moderate levels of death anxiety (56.5%) and very good quality of life (75.9%). Pearson's correlation test showed a very strong and significant negative relationship between death anxiety and quality of life (r = -0.814; p = 0.000). The higher the level of death anxiety, the lower the patient's quality of life. Psychological intervention is needed to reduce death anxiety and improve the quality of life of patients.